Shades of darkness - Kahler, A. R. (New York : Simon Pulse, 2016)
As she discovers the truth about her past, Kaira, a senior at a boarding school for aspiring musicians and artists, discovers that vengeful gods are threatening humanity.
Ages 14 up.
Keywords: Gods -- Fiction; Occultism -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Artists -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Social Issues / Dating & Sex